2020
DOI: 10.1016/j.pursup.2020.100610
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Ambidexterity and IT competence can improve supply chain flexibility? A resource orchestration approach

Abstract: Supply chain flexibility (SCF) has become an important competitive weapon for companies in the current dynamic environment. This paper explores the influence of ambidexterity on supply chain flexibility (SCF) and theorizes the moderating effect of information technology (IT) competence on that relationship. Whereas prior research focuses on the positive results of SCF for business performance, little empirical research has studied its facilitators, leaving the gap this study seeks to fill. We draw on resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 105 publications
5
32
0
Order By: Relevance
“…Our findings indicate that the coexistence and combination of executives' awareness of environmental risks and benefits promote the ability of enterprises to implement supply chain strategies for improving economic outcomes and environmental performance. Our results are in accordance with prior researches that the cognition of executives and organizational ambidexterity are crucial to the implementation effect of enterprise strategies (Gallego Burin, Perez‐Arostegui, & Llorens‐Montes, 2020; Sen, Kotlarsky, & Budhwar, 2020). The event that Gree reported Aux making the false propaganda of the energy efficiency level in June 2019 also provides evidences for the significance of combined ambidexterity of executives' awareness.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings indicate that the coexistence and combination of executives' awareness of environmental risks and benefits promote the ability of enterprises to implement supply chain strategies for improving economic outcomes and environmental performance. Our results are in accordance with prior researches that the cognition of executives and organizational ambidexterity are crucial to the implementation effect of enterprise strategies (Gallego Burin, Perez‐Arostegui, & Llorens‐Montes, 2020; Sen, Kotlarsky, & Budhwar, 2020). The event that Gree reported Aux making the false propaganda of the energy efficiency level in June 2019 also provides evidences for the significance of combined ambidexterity of executives' awareness.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, specific actions by the managers are required to orchestrate a set of resources to assist the value creation by the firms ( Hitt, 2011 ; Sirmon et al, 2011 ). Since then, resource orchestration theory has been successfully used in different supply chain and operations management approaches ( Gong et al, 2018 ; Liu et al, 2016 ; Rojo Gallego Burin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we found that blockchain technology increases supply chain flexibility. More flexible supply chains can better meet customer demands [41] and better tackle the volatile and uncertain environments [43]. Real-time data sharing will be enabled in supply chains using blockchain technology [19].…”
Section: Discussion: Blockchain Technology and Supply Chain Integration In Terms Of Supply Chain Dynamicsmentioning
confidence: 99%
“…Governments can also utilize flexibility in the field of information to adapt and respond quickly to change due to the absence of good information [42]. Creating a flexible supply chain is key to achieving a sustainable competitive advantage in today's environment, characterized by dynamism, uncertainty, and unpredictability [43]. A flexible supply chain improves the delivery process and quickly transports products to market in required quantities [44].…”
Section: Blockchain Technology and Supply Chain Flexibilitymentioning
confidence: 99%